Typologie hodnotících postojů k drogám v sociální práci - Duplinský, Josef (Univerzita Pardubice, 2007)
This article attempts to categorise the attitudes of the public and professional personnel involved in legalising certain drugs.The categories are presented in opposing views, i.e. the most frequent arguments for legalisation are cited on one side and the other standpoints regarding the relevant questions are on the other.
Keywords: legalisation; drugs; attitudes; bipolarity; social work